Quantitative evaluation of defensive performances in handball game using attractive rate - Yoshino, K.; Zhang, S.; Hayashi, K.; Takahashi, K. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Ball games such as soccer and handball are played with teamwork. When planning a game strategy, it is more important to analyze both teams formation than to analyze individual player's personal performance. We have introduced the concepts of a key player and an attractive rate [1]. The key player is the last passer who passes a ball to the shooter. The attractive rate expresses quantitatively the change of the position of all defenders by the movement of the last passer. In this paper, we investigate the relationship between the defensive performance and the team level by computing the attractive rate in three games between the criterion team and the teams with different levels. Methods The attractive rate is obtained from the position of the last passer and that of all defenders excluded the keeper. The position of players on a handball court can be computed from the recorded video images of a game by the method of 2 Dimensional Direct Liner Transformation (2D-DLT). The attractive rate (Ra) is computed from the equation Ra=100(DRec-DPas)/DRec, where DPas is the sum of the distances between the position of the last passer and that of all opponent defenders when the last passer passes a ball to the shooter, and DRec is the sum of the distances between the position of the last passer when he passes the ball to the shooter and that of all opponent defenders when the last passer receives the ball. The attractive rate will become large, if the last passer attracts many defenders to him. We analyzed handball games in the men's first division of Japan handball league. The subject games of investigation were a criterion team versus three teams that have the lower level, the higher level and the same level compared with the criterion team, respectively. The shoot scenes were extracted by editing the video images of the games. Here, the analyzed shoot scenes did not include those with a fast break or those where the last passer passes the ball without movement. Results Graph 1 shows the change of the attractive rate of three games. The vertical axis represents the attractive rate. And the horizontal axis represents the distance from the position of the last passer to the goal at the time when he passes a ball Discussion / Conclusions As shown in graph 1, defenders in every level team are not influenced by the movement of the last passer, if the last passer is in a position far removed from the goal; however, as the playing area of the last passer approaches the goal, the attractive rate of the lower level team becomes large. This is because defenders in the lower level team become sensitive to the movement of the last passer than that of a marking player. The result suggests that the lower level team gives the chance to be in free position to more offenders in the opponent team and loses the game. Thus, our introduced attractive rate is utilized for evaluating the defensive performance.